Influenced of the Liquid Chaya Leaves (Cnidoscolus aconitifolius) Supplementation on Growth Performance of the Quails - Raynesa Nurul Nurjanah; Widya Hermana; Yuli Retnani (Faculty of Animal Science, Universitas Brawijaya, 2023)
The purposed of this study was to analysed the influenced of liquid Chaya leave (Cnidoscolus aconitifolius) to drinking water of quail starter. A total 30 Day-Old-Quail (DOQ) were used in this research. The experimental design in this study used a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatment consisted T0 = control; T1 = drinking water added Vita Chick; T2 = drinking water containing 2,5% chaya leaves extract; and T3 = drinking water containing 5% chaya leaves extract. Data were analyzed by analysis of variance (ANOVA), if there were significantly different results, Duncan's test was performed. The study showed that chaya leaves extract supplementation had no significant effect (p >0.05) for water intake, feed intake (FI), body weight (BW), feed conversion ratio (FCR) and mortality of quail starter. In summary, Chaya leaves infusion supplementation as much as 2.5% and 5% through drinking water with a frequency of twice a week has the best body weight gain and feed conversion ratio. Further research is needed regarding the effect of administering chaya leaves infusion, and the concentration of chaya leaves infusion on the laying period of quail eggs.